Superradiance : energy extraction, black-hole bombs and implications for astrophysics and particle physics /: energy extraction, black-hole bombs and implications for astrophysics and particle physics. (2015) - Brito, Richard; Cardoso, Vitor; Pani, Paolo
No abstract available